Carriage Methicillin-Resistant Staphylococcus aureus in Poultry and Cattle in Northern Algeria - Saliha Bounar-Kechih; Mossadak Taha Hamdi; Hebib Aggad; Nacima Meguenni; Zafer Cantekin (Veterinary Medicine International)
Multiresistant and especially Methicillin-Resistant Staphylococcus aureus (MRSA) poses a serious public health problem that requires their immediate identification and antibiotic resistance characteristics. In order to determine antibiotic resistance S. aureus poultry and bovine origin, 8840 samples were collected from slaughterhouses in the northern region of Algeria between years 2009 and 2014. 8375 samples were from an avian origin (1875 from laying hens and 6500 from broiler chickens) and the rest was from bovine origin. Bacteriological isolation and identification were made by classical culture method and antibiotic resistance patterns were determined by disc diffusion test. The prevalence of S. aureus was 42% in laying hens, 12% in broilers, and 55% in bovine samples. The prevalence of MRSA was 57%, 50%, and 31% in laying hens, broiler chickens, and bovine, respectively. While MRSA strains isolated from poultry showed cross-resistance to aminoglycosides, fluoroquinolones, macrolides, sulphonamides, and cyclins, those isolated from bovine also revealed similar multiresistance except for sulphonamide. This high percentage of methicillin resistance and multidrug resistance in S. aureus poultry and bovine origin may have importance for human health and curing of human infections.